Alert for pharynx-centered gastrointestinal and respiratory cross-infection and cryptic cross-transmission routes of 2019-nCoV - Chen, Xiehui; Wang, Zhanke; Wang, Jiaxuan; Zhu, Zhongzhen; Li, Chunxin; Hu, Tian (The Journal of Infection in Developing Countries, 2024)
We proposed that the pharynx, as a common organ of the respiratory and digestive tracts, may be a respiratory and digestive tract cross cryptic transmission pathway for 2019-nCoV infection from the nasal cavities to the pharynx and lung, then to nasal cavities by aerosol (respiratory route) to the pharynx and the gastrointestinal tract, then to the oral cavity by feces (fecal-oral route) and to pharynx, lungs, or gastrointestinal tract.